Uji Aktivitas Antibakteri Sediaan Gel Ekstrak Etanol Daun Rimbang (Solanum Torvum Swartz) terhadap Bakteri Propionibacterium Acnes: Antibacterial Activity Test of Ethanol Extract Gel Preparation of Rimbang Leaves (Solanum Torvum Swartz) against Propionibacterium Acnes Bacteria - Nurjannah, Sofia; Kusumastuti, Melati Yulia; Safriana, Safriana; Tanjung, Siti Aisyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The skin is the outermost part of the body that limits it from the human environment. Damage to the skin glands can cause skin disorders, one of which is acne. The bacteria that cause acne are Propionibacterium acnes bacteria. Antibiotics are needed to inhibit bacterial growth, but improper use can cause side effects. The purpose of this study was to explore the antibacterial activity of the ethanol extract gel preparation of rimbang leaves (solanum torvum swartz) against propionibacterium acnes bacteria. This research method is with an experimental quantitative approach. The stages of the study include screening of powdered simplicia and ethanol extract, Formulation of gel preparations without test materials and ethanol extract of rimbang leaves (EEDR) 10%, 20%, 30%, Evaluation tests of the preparations include: organoleptic, homogeneity, stability, adhesion, spreadability, viscosity, pH, irritation, and preference. Then the antibacterial activity test uses the well method. The results showed that the screening results on powdered simplicia and ethanol extract met the physical quality requirements of secondary metabolite compounds. The results of the antibacterial activity of EEDR 30% bacterial inhibition diameter of 14.33 ± 8.72. EEDR 20% produced a bacterial inhibition diameter of 12 ± 11.4. EEDR 10% produced a bacterial inhibition diameter of 10.67 ± 8.70. While the blank produced a bacterial inhibition diameter of 6.33 ± 3.26. From this study it can be concluded that the preparation of ethanol extract gel of rimbang leaves has inhibitory activity against Propionibacterium acnes bacteria.